(3GdJbfjGJ GdHfcjI (B:s (3eMGVQGJ hJWHjbGJ (B/s - (3aVjd, aGQSs ((3GdLRGFQ(B: s (3GdehSGc QTjO(B, s, 2013)
(3gPG GdLRA GdGhd ef GdcJGH jJcde ajg GdcGJH Yf (B: (3eGgjI GdHfc hhXGFag hCfhGYg GdGgOGa GdeNJdaI GGHfc , GdOhQ GdLhgQj ddHfc , echfGJ GdLgGR GdHfcj , JWhQGJ GdfXGe GdHfcj GdLRGFQj GdYed GdHfcj TQhWg eNGWQg hGdJWhQGJ GdHfcjI GdYGdejI GdQGgfI COhGJ GdOaY GdHfcjI GdJbdjOjI GdMSGH GdHfcj , GdfbhO GdbGfhfjI hfbhO GdhOGFY GdGhQGb GdJLGQjI , GdJMhjd hGdGbJWGY , GdebGUI GdUjQGaI GdGdcJQhfjI hCOhGJ GdOaY GdGdcJQhfjI GdHfhc GdGdcJQhfjI , GdHWGbI GdHfcjI , GdfbhO GdGdcJQhfjI hSGFd GdOaY GdGdcJQhfjI GdGNQi , JLQHI GdLRGFQ aj gPG GdeLGds
(3edGMb U(B. 333 (3HjHdjhZQGajG U(B. 341s
Keywords: (3GdGhQGb GdJLGQjIs; (3GdGhQGb GdJLGQjI GdGdcJQhfjIs; (3GdHWGbGJ GdHfcjIs; (3GdLRGFQ (B-(3GdHfhcs; (3GdbQhVs; (3GdeUGQas